A content validity and cognitive interview to develop the HARMONI items: Instrument measuring student well-being in West Java, Indonesia - Susanto, Hery; Wedyaswari, Miryam; Dalimunthe, Karolina Lamtiur (Frontiers in Education, 2023)
Practitioners in education need student well-being measures to measure the “skills of well-being.” These skills should be taught in school alongside achievement skills to improve the learning process and student outcome. However, most existing well-being instruments are designed for the western population, even though geographic regions and cultural diversities are important to consider to develop well-being instruments. Thus, we use the PROSPER (Positivity, Relationship, Outcomes, Strength, Purpose, Engagement, Resilience) model as a student well-being framework to develop an instrument named the HARMONI (Hasil yang berproses, Andal berdaya lenting, Relasi yang positif, Makna dalam tujuan, Orientasi sikap positif, Nilai suatu kekuatan, Inisiatif yang melibatkan), which is specified for West Java high school student population. The HARMONI instrument has seven dimensions: Positivity, Relationships, Outcomes, Strengths, Purpose, Engagement, and Resilience. The study aims to develop HARMONI items for high school students in West Java. We conducted three activities: item development, expert reviews, and cognitive interviews. In the review process, nine experts in total who are experts in educational psychology, well-being, and psychometry were involved. Based on the reviews, we reduced the items from 556 to 125 items. The calculation of the Content Validity Index of the reviews showed that the items have good content validity (mean I-CVI ranging from .96 to 1). Next, cognitive interviews were conducted to analyze participants' cognitive processes in responding to the items. The participants of the cognitive interviews were 25 senior high school students in West Java, who were selected based on a purposive sampling technique. The result showed that the participants well understood most of the items. However, several items needed to be revised due to problems related to comprehension, retrieval, and judgment. The items were improved by changing incomprehensible, vague, and ambiguous words, revising the sentence structure, and adding more specific cues. A total of 124 items were ready to be used for a psychometric study.